LOKAKARYA PENINGKATAN PARTISIPASI REMAJA DALAM PENGEMBANGAN POTENSI DESA - Endang Dwi Wahyuningsih; Yetti Iswahyuni; Praditya Dewi Arumsari; Mudjiyono Mudjiyono; Yoto Yoto; Agustinus Wardi; Purnomo Y.A (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
This community service aims as village development literacy for the Village Head, Village Officials and Village Youth. The workshop was held in Bandungan, Semarang Regency, and program implementation was carried out in 5 selected districts in Central Java Province. This activity is supported by LPPM ITB Semarang and Unicef, which is included in the Program for Handling Out of School Children in Central Java Province. Through the lecture method with visual media supporting devices and ending with a question and answer session, it is very effective in delivering material. This was shown by the enthusiasm of the participants in the question and answer interaction at the discussion forum.